STUDI IN SILICO PEMBENTUKAN KOKRISTAL MELOXICAM DENGAN BERBAGAI KOFORMER PERBANDINGAN (1 : 1) - Yuli Ainun Najih; Farizah Izazi; Siswandono Siswandono; Bella Anggraini Putri (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Cocrystal is one form of modification in increasing the solubility of meloxicam which is included in Biopharmaceutics Classifications System (BCS) II. Cocrystal is a multicomponent system with a stoichiometric ratio between the active ingredient and the coformer which are bound in the crystals lattice to form hydrogen bonds. Design of new drugs can be done through an in silico program to optimize the parent compound before the synthesis of derivative compounds. This study aims to predict which coformers are most stable in the formation of crystals. Cocrystal formation is done by drawing a two-dimensional structure from meloxicam and coformer using ChemBioDraw Professional 16.0 software from CambridgeSoft®. The prediction will result in the amount of bond energy formed between meloxicam with coformer. The smaller the bond energy, the more stable the meaning of the bond. The smaller the bond energy formed, the more stable the bond is. Stable bonds have a high probability of forming cocrystals meloxicam. Hydrogen bonds occur between hydrogen atoms and other atoms that have high electronegativities such as O and N atoms which have lone pairs of electrons. This electronegativity difference makes H atoms tightly bound to O and N atoms so that the hydrogen bonds in the meloxicam cocrystal are tightly bound and stable. From the results of the study showed that the most stable coformer can form cocrystals with a small bond energy that can produce bonds with meloxicam, namely urea.